Relationships between Exclusive Breastfeeding, and History of Illness, and Stunting in Children Under Five - Picauly, Intje (Journal of Maternal and Child Health, 2023)
Background: Exclusive breastfeeding can affect a child’s immune system against infectious diseases and malnutrition. Children under five who experience repeated infectious diseases and malnutrition will have the opportunity to experience stunting problems. Riskesdas (2018) shows that the prevalence of stunting under five in the Province of East Nusa Tenggara (NTT) is higher (42.6%) than the average prevalence of stunting in Indonesia (30.8%). The results of the initial survey found that the coverage of exclusive breastfeeding was very low and the morbidity rate for children under five was still high in the Working Area of the Kokar Health Center, Alor Barat Laut District, Alor Regency, NTT. Subjects and Method: A case control study conducted in Adang Village, the work area of the Kokar Health Center, Alor Barat Laut District, Alor Regency in October-November 2021. The size of the study sample was 132 toddlers with 66 case samples and 66 control samples taken by simple random sampling. The dependent variable was the incidence of stunting. The independent variables were the history of exclusive breastfeeding and the history of illness. The analysis used is simple logistic regression analysis and followed by Odd Ratio (OR) analysis. Results: The history of exclusive breastfeeding (OR=4.57; CI95%= 1.58 to 13.21; p= 0.003) and the history of illness (OR=5.33; CI95%= 2.53 to 11.24; p <0.001) were associated with the incidence of stunting. Further test results showed that every child under five who had a history of bad exclusive breastfeeding had a 4.5 times greater risk of experiencing stunting and a child under five who had a history of illness more often had a 5.3 times greater risk of experiencing stunting. Conclusion: The incidence of stunting in the Northwest Alor District, Alor Regency, NTT Province is influenced by a history of exclusive breastfeeding and a history of infectious diseases or illness. Keywords: history of exclusive breastfeeding, history of illness, incidence of stunting, infectious diseases, nutritional intake Correspondence: Intje Picauly, Department of Nutrition, Faculty of Public Health, Universitas Nusa Cendana, Kupang City, East Nusa Tenggara, Indonesia, Jl. Adi Sucipto Penfui, Penfui, Maulafa, Kupang, Nusa Tenggara Timur.